Pembelajaran Bahasa Daerah dalam Upaya Mengenalkan Keragaman Bahasa Daerah Indonesia di Sanggar Bimbingan Rawang, Selangor, Malaysia - Wahdaniah, Wini; Nur, Hana Astria; Hermawan; Heriyana, Tio; Hadiana, Oman (Jurnal Pengabdian Tri Bhakti, 2024)
The Indonesian nation is a nation that is very rich in differences and equality as stated in the motto "Bhineka Tunggal Ika". One of the diversities is the regional language. Regional languages ​​need to be preserved so that their completeness is maintained like Sundanese. Sundanese is a regional language of West Java which is a characteristic of the Indonesian people who live in it. The purpose of implementing this regional language learning is intended to introduce one of the many regional languages ​​in the archipelago and provide an interesting and meaningful language learning experience. The benefits of learning Sundanese in SB Rawang, Selangor, Malaysia are able to provide broader knowledge and language skills for students. In this study, the researcher provided an introduction to the Sundanese regional language by using the song method, namely through the song "Manuk Dadali" which is a typical song of the West Java region. The respondents in this study were 15 people who were students in grades V and VI. The steps in implementing this research were through the process of preparing plans, implementing activities and also conducting evaluations as reflections. The results obtained showed that the results related to knowledge about regional languages ​​in grades V and VI of SB Rawang, Selangor, Malaysia were still very minimal and low. After the learning process shows high motivation and interest from students to learn regional languages. This is shown by their enthusiasm when Sundanese language learning takes place, their enthusiasm is extraordinary.